Arrangement of Access to the Religious Tourism Area of The Tomb K.H. Abdurrahman Wahid Jombang Regency - Achdan, Syada Taruna; Solichin, Ibnu; Estikhamah, Fithri (Universitas Negeri Padang, 2024)
Jombang Regency is one of the regencies in the East Java region that boasts numerous tourist destinations. One of the religious attractions in Jombang Regency is the Tomb of K.H. Abdurrahman Wahid. Suboptimal road traffic conditions occur in the tourism area, particularly on K.H. Hasyim Asyari Street. This road segment frequently experiences high traffic volume due to tourism activities, numerous obstacles such as roadside parking, and non-motorized vehicles moving around the tourism area. This research adheres to the Guidelines for Indonesian Road Capacity (PKJI) 2014 regarding Urban Road Capacity. The primary data required for this study include geometric road data, traffic volume data, and roadside obstacle data. Meanwhile, secondary data in this study comprise road network data and Average Daily Traffic (ADT) data from the relevant authorities, namely the Jombang Regency Transportation Agency. From the traffic performance calculations, the saturation degree values for the existing conditions on K.H. Hasyim Asyari Street towards the south (DJ) = 0.7624 and towards the north (DJ) = 0.7075 were obtained. Based on the survey results, K.H. Hasyim Asyari Street towards the north has a capacity (C) = 2465, and towards the south, it also has a capacity (C) = 2465. The parking space requirements in the Religious Tourism Area of the Tomb of K.H. Abdurrahman Wahid (Gus Dur) are planned to be 171 parking spaces for motorcycles, 54 parking spaces for cars, and 53 parking spaces for buses.